Clinical factors associated with the development of atrial fibrillation in the year following STEMI treated by primary PCI. Issue 2 (February 2018) - Rhyou, Hyo-In; Park, Tae-Ho; Cho, Young-Rak; Park, Kyungil; Park, Jong-Sung; Kim, Moo-Hyun; Kim, Young-Dae
Highlights: Cardiogenic shock was a strong predictor of new-onset AF in STEMI patients. LA volume was significantly associated with the development of new-onset AF in STEMI patients. Abstract: Background: Advanced age, poor left ventricular function, and congestive heart failure are known predictors of atrial fibrillation (AF) in acute myocardial infarction (AMI) patients. Recent advances in AMI treatment may have changed the occurrence of new-onset AF. Thus, we investigated the factors associated with the development of new-onset AF in ST elevation myocardial infarction (STEMI) patients. Methods: This study included 527 STEMI patients [mean age, 60.6 ± 12.8 years; 102 (19.4%) women] who underwent primary percutaneous coronary intervention (PCI) in the previous 7 years. New-onset AF was evaluated following STEMI treated by primary PCI. Patients who developed AF during this follow-up period were compared with those who did not develop AF to identify factors that were associated with the development of AF. Results: New-onset AF was documented in 81 patients (15.4%) at 1 year after STEMI. Patients with new-onset AF ( n  = 81) tended to be older ( p  < 0.001); were more often female ( p  = 0.009); had more congestive heart failure ( p  = 0.015); had less use of beta-blockers ( p  = 0.001); had more often used antiarrhythmic drugs ( p  < 0.001); experienced cardiogenic shock more frequently ( p  = 0.038); had lower left ventricular ejection fraction ( p  = 0.024); and had higher E velocity ( p  < 0.001), E/e′ ( p  = 0.011), and left atrial volume index (LAVI; p  = 0.029) than the 446 patients with no AF. Multivariate regression analysis revealed that cardiogenic shock, LAVI, and age were predictors of new-onset AF in STEMI patients (OR 2.823, 1.254, and 1.124; p  = 0.005, <0.001, and 0.028, respectively). Conclusion: Cardiogenic shock was a new predictor of new-onset AF in STEMI patients.